2016
DOI: 10.1590/0103-6440201600899
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes in BMP4 and FGF Genes Increase the Risk of Peri-Implantitis

Abstract: Despite the success of osseointegrated implants, failures have increased significantly, associated with development of peri-implantitis. Multiple factors influence the peri-implant bone loss, including environmental and genetic causes. BMPs (Bone morphogenetic proteins) are growth factors that induce bone formation. FGF (fibroblast growth factors) and their receptors (FGFRs) play important roles by controlling the levels of cell proliferation, differentiation and migration. BMP/FGF relationship is responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Clinicians should keep in mind that BMP signaling plays a role in fracture healing and orthodontic tooth movement, when correcting the distal relationship and distal occlusion (Guimarães et al, 2013). An increased risk of peri-implantitis was found in BMP4 haplotypes (Coelho et al, 2016). This must be taken into account when clinicians consider replacing missing teeth by implants.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should keep in mind that BMP signaling plays a role in fracture healing and orthodontic tooth movement, when correcting the distal relationship and distal occlusion (Guimarães et al, 2013). An increased risk of peri-implantitis was found in BMP4 haplotypes (Coelho et al, 2016). This must be taken into account when clinicians consider replacing missing teeth by implants.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation reported remarkably association with additional candidate genes. Coelho et al investigated the association between peri‐implantitis and bone morphogenetic proteins or fibroblast growth factor because of their involvement in bone remodeling. This study, involving 215 patients, found elements supporting a possible role for bone morphogenetic protein‐6 and fibroblast growth factor‐10 in peri‐implantitis.…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“… There is high level of RANKL/OPG in peri‐implant mucosae of patients with history of chronic periodontitis (Costa et al., ). Haplotypes in BMP4 and FGF genes increase the risk of peri‐implantitis (Coelho et al., ) MMP13 , TIMP2, and TGFB3 gene polymorphisms are associated with Brazilian chronic periodontitis and peri‐implantitis (Junior et al., ). BRINP3 gene has different contribution in chronic periodontitis and peri‐implantitis (Casado et al., ). IL6 gene polymorphism is associated with periodontitis and peri‐implantitis in a Brazilian population (Casado et al., ,b). …”
Section: Periodontitis and Peri‐implant Diseasesmentioning
confidence: 99%
“…and FGF genes increase the risk of peri-implantitis (Coelho et al, 2016) 3. MMP13, TIMP2, and TGFB3 gene polymorphisms are associated with Brazilian chronic periodontitis and periimplantitis .…”
Section: Haplotypes In Bmp4mentioning
confidence: 99%